2021
DOI: 10.30953/bhty.v4.182
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Blockchain Technology for Informed Consent Process and Patient Engagement in a Clinical Trial Pilot

Abstract: Objective: Despite the implementation of quality assurance procedures, current clinical trial management processes are time-consuming, costly, and often susceptible to error. This can result in limited trust, transparency, and process inefficiencies, without true patient empowerment. The objective of this study was to determine whether blockchain technology could enforce trust, transparency, and patient empowerment in the clinical trial data management process, while reducing trial cost. Design: In this proof … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Alternative approaches to develop technologies for improving patient engagement in research are focused on clinical research, 21 where patients are active participants. By contrast, most organoid research activity uses de-identified samples, and translational scientists are not accustomed to communicating with patients, who may not be aware of the nature of their contributions to biobanking after one-time broad consent.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative approaches to develop technologies for improving patient engagement in research are focused on clinical research, 21 where patients are active participants. By contrast, most organoid research activity uses de-identified samples, and translational scientists are not accustomed to communicating with patients, who may not be aware of the nature of their contributions to biobanking after one-time broad consent.…”
Section: Discussionmentioning
confidence: 99%
“…Data also suggests that blockchain technology reduces monitoring visit time and cost while improving patient trust and sense of empowerment compared to conventional clinical trial management. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, using a blockchain system, patients opt‐in and wait for notification of matched potential eligible trials to participate. 59 , 60 , 61 …”
Section: Strategies To Increase Patient Participationmentioning
confidence: 99%
“…Selected patients will be notified by the master smart contract for availability of clinical trials and for patient authorization to allow the eligible trial sponsor to access their electronic health records to double check recruitment criteria. Therefore, using a blockchain system, patients opt‐in and wait for notification of matched potential eligible trials to participate 59–61 …”
Section: Strategies To Increase Patient Participationmentioning
confidence: 99%
See 1 more Smart Citation